2022
DOI: 10.1111/jjns.12473
|View full text |Cite
|
Sign up to set email alerts
|

Hospital organizational structure factors related to discharge planning activities for alcoholics by nurses in Japan

Abstract: Aim: Nurses play a significant role in providing discharge support for alcoholics. We aimed to explore the organizational structures of hospitals that are related to effective discharge planning activities provided by nurses. Methods: We conducted a cross-sectional survey of Japanese hospitals with psychiatric wards that accept alcoholics. The survey questionnaire was administered to one nurse per hospital from August to September 2019. The Discharge Planning Scale for Ward Nurses (DPWN) was used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition to patient safety, the researches on patient discharge are also important in the field of nursing. This topic mainly focuses on the influencing factors of patient readiness for hospital discharge, where SEM is needed for validating relative instrument regarding patient readiness for hospital discharge and analyzing the multivariate influences on it (Adachi et al, 2022;Galvin et al, 2017;Mabire et al, 2019). The cluster of "cross-cultural comparison", "benchmarking", and "psychometrics" indicated that the application of the multi-group invariance testing is common in the nursing field.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to patient safety, the researches on patient discharge are also important in the field of nursing. This topic mainly focuses on the influencing factors of patient readiness for hospital discharge, where SEM is needed for validating relative instrument regarding patient readiness for hospital discharge and analyzing the multivariate influences on it (Adachi et al, 2022;Galvin et al, 2017;Mabire et al, 2019). The cluster of "cross-cultural comparison", "benchmarking", and "psychometrics" indicated that the application of the multi-group invariance testing is common in the nursing field.…”
Section: Discussionmentioning
confidence: 99%